2003
DOI: 10.1093/brain/awg065
|View full text |Cite
|
Sign up to set email alerts
|

The effect of negative emotional context on neural and behavioural responses to oesophageal stimulation

Abstract: Sensory experience is influenced by emotional context. Although perception of emotion and unpleasant visceral sensation are associated with activation within the insula and dorsal and ventral anterior cingulate gyri (ACG), regions important for attention to and perception of sensory and emotional information, the neural mechanisms underlying the effect of emotional context upon visceral sensation remain unexplored. Using functional MRI, we examined neural responses to phasic, non-painful oesophageal sensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(120 citation statements)
references
References 54 publications
7
110
1
1
Order By: Relevance
“…The decision to continue with analysis and interpretation on seven subjects was based on several reasons: 1) Brain activity reported in the present experiment is analogous to previous studies that demonstrated that between six to eight volunteers provide adequate statistical power to produce a network of brain activity consistent with that of pain processing (3,25,53,68). 2) It is also important to note the consistency in activation across four intensities of stimulation and three scanning sessions.…”
Section: Limitationssupporting
confidence: 53%
See 1 more Smart Citation
“…The decision to continue with analysis and interpretation on seven subjects was based on several reasons: 1) Brain activity reported in the present experiment is analogous to previous studies that demonstrated that between six to eight volunteers provide adequate statistical power to produce a network of brain activity consistent with that of pain processing (3,25,53,68). 2) It is also important to note the consistency in activation across four intensities of stimulation and three scanning sessions.…”
Section: Limitationssupporting
confidence: 53%
“…However, data from the present study show that insula activity is consistent, regardless of stimulation level, suggesting that this region does not encode the intensity of visceral sensation. It may be more likely that the role of the anterior insula is in processing emotional responses to visceral sensation, as some previous studies suggest (51,53).…”
Section: Effect Of Stimulus Intensitymentioning
confidence: 80%
“…Therefore, our results may suggest the importance of the insula, ACC, MCC and midFC in dyspepsia-related sensations. In a previous study, Phillips et al 27 showed significantly higher brain activation in the insula and ACC as well as significantly greater discomfort and anxiety during esophageal stimuli with fearful faces than with neutral faces, providing first evidence for the neural mechanism underlying the influence of emotional context on symptoms in functional disorders. Although our results may not directly verify the role of psychological factors in visceral sensation, we showed the overlapping regions between dyspepsia symptoms and anxiety/depression.…”
Section: Discussionmentioning
confidence: 87%
“…Psychological factors are considered to play a major role in mediating the differences in pain perception observed between men and women (23) and also influence the brain processing of pain (11,22,(42)(43)(44)54). For instance, it has been reported that personality, in particular neuroticism, modulates the brain processing of visceral pain and anticipation of pain (11).…”
Section: Psychophysiological Factorsmentioning
confidence: 99%
“…The posterior insula processes information about the physiological condition of the body, whereas the anterior insula cortex processes subjective feelings from the body and emotional awareness through interoception (13). Activity in the anterior insula increases when visceral pain is delivered during negative emotional arousal (12,42). Mayer et al (34) have proposed a concept of homeostatic emotions, which are the motivations and feelings associated with changes in the body's physiological condition and are the background emotions that affect our mood and disposition.…”
Section: Brain Processingmentioning
confidence: 99%